The effectiveness of bandwidth knowledge of results on a throwing task in goalball players with visual impairments - Nir Dov Shimony; Ronnie Lidor; Gal Ziv (European Federation of Adapted Physical Activity, 2020)
The purpose of the current study was to examine whether a wide bandwidth knowledge of results (WBWKR) would result in better throwing accuracy and consistency compared to a narrow bandwidth knowledge of results (NBWKR) among goalball players with visual impairments. Elite goalball players (n=14) were randomly assigned to one of two groups - a WBWKR or a NBWKR group. The participants practiced a throwing task on a goalball court with either a wide bandwidth (1.98 m) or a narrow bandwidth (1.5 m) target. They completed the task at pre-test and acquisition phases. Seventy-two hours after the participants completed the acquisition trials, they performed retention and transfer tests. It was found that in the transfer test, the number of target hits was significantly greater and the absolute error was significantly smaller in the WBWKR participants than in the NBWKR participants. We conclude that goalball players could benefit from the use of WBWKR when practicing throws at the goal.